Le plaisir des sens comme source de bonheur dans les Stultiferae naves de Josse Bade et l'Éloge de la Folie d'Érasme - Duhl, Olga Anna (Renaissance and Reformation / Renaissance et Réforme, 2006)
The pursuit of happiness represents one of the major paradoxes of Erasmus' best-known work, Encomium Moriae (The Praise of Folly) (1511). While spiritual bliss is upheld as the ultimate form of happiness, the speaking subject celebrating it, who is no other than Folly herself, also argues for the superiority of the pleasures derived from the five senses. The narrative strategy which helps to maintain such an ambiguous position with regards to the ideal form of happiness, however, was scarcely Erasmus' invention, although he has been traditionally credited for it. As shown by the present comparative analysis, the praise of sensory pleasure through the mouth of Folly can be found in a nearly contemporary source, the Stultiferae naves (The Ship of Foolish Maidens) (1501). This work was probably well-known to Erasmus, since it belonged to the famous early-humanist printer, editor, commentator, and author Jodocus Badius Ascensius, who was also his principal Parisian editor until a regrettable event put an end to their relationship.